KONTRIBUSI SERSAN DUA YOHANAS OEMAR DALAM KONTINGEN GARUDA VIII DI TIMUR TENGAH 1978-1979 - Elna, Fitri; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Yohanas Oemar is a Struggling Learner in Developing Education. In order to fulfill his desire to deepen his knowledge, he willingly tried to persevere and to get what he wanted, as long as the status of students at the University of Riau, he also active in various Campus Organizations, as a student at the Faculty of University of Riau he followed the entrance to the University Student Regiment Riau and became a Member of the Student Regiment. From Member of Student Regiment he got the Opportunity to join Candidate School in Bandung Pangalengan, Yohanas Oemar Graduated School of Candidate with the rank of Second Sergeant, He also get the Opportunity to Contribute to Middle East Peace Sinai joined in Garuda Indonesia Ind Bat Force under UN auspices . And He is in Nobat As Veteran of Peace. This study aims to find out the biography of Yohanas Oemar, Sgt Sergeant's Contribution Two Garuda VIII Contingent as UN Peacekeepers in the Middle East, knowing the end of Yohanas Oemar's Struggle. The method used is the Method of History, namely by using Interview Techniques, Techniques Library Studies, and Documentation. The result of this research is that Yohanas Oemar was born in Strait of Panjang Meranti on 07 Mai 1956 and died on June 25, 2017 is buried in Kahluma Dharma Pahlawan Pekanbaru. During his lifetime he spent his time developing education, the initial struggle of the status of a student into the command of the Riau University Student Regiment running Education Becomes TNI, besides he is also active in various social activities, and he also works in various fields, the board of Black Belt Board Karate Do Tako Riau , Chairman of the Organization for the Riau Forki, and Chairman of the Division of DPD Alumni Menwa Indonesia Riau. besides that he is also an Active Lecturer at the University of Riau.Keywords: Yohanas Oemar, Kontingen Garuda VIII, Timur Tengah